2017
DOI: 10.1021/acsami.7b08489
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Effects of Metallic Nanoparticles on Enhancing Performance of Perovskite Solar Cells

Abstract: We report systematic design and formation of plasmonic perovskite solar cells (PSCs) by integrating Au@TiO core-shell nanoparticles (NPs) into porous TiO and/or perovskite semiconductor capping layers. The plasmonic effects in the formed PSCs are examined. The most efficient configuration is obtained by incorporating Au@TiO NPs into both the porous TiO and the perovskite capping layers, which increases the power conversion efficiency (PCE) from 12.59% to 18.24%, demonstrating over 44% enhancement, compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
81
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(82 citation statements)
references
References 56 publications
0
81
1
Order By: Relevance
“…To increase the PCE of PSCs as a result of enhanced optical absorption of the incident light, the incorporation of plasmonic NPs such as (Ag and Au) is a very fascinating approach . A very first report of plasmonic nanostructures incorporated into PSCs was by Snaith and co‐workers in 2013.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase the PCE of PSCs as a result of enhanced optical absorption of the incident light, the incorporation of plasmonic NPs such as (Ag and Au) is a very fascinating approach . A very first report of plasmonic nanostructures incorporated into PSCs was by Snaith and co‐workers in 2013.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] To increase the PCE of PSCs as a result of enhanced optical absorption of the incident light, the incorporation of plasmonic NPs such as (Ag and Au) is a very fascinating approach. [21][22][23] A very first report of plasmonic nanostructures incorporated into PSCs was by Snaith and co-workers in 2013. They used Au@SiO 2 NPs incorporated into mesostructured Al 2 O 3 , causing the PCE to increase from 8.5% to 9.5%.…”
Section: Introductionmentioning
confidence: 99%
“…Among these techniques, the plasmonic nanoparticle approach is considered to be the best one as it utilizes surface plasmons to enhance the absorption in the active layer of the solar cell. [7][8][9] Recently, it has been found that cadmium telluride (CdTe) is the most promising candidate for the active layer among thin-lm solar cells due to its long-term stability and capability of photon absorption in visible and near infrared region. 10 Furthermore, it is a direct bandgap semiconductor with optical absorption coefficient of 10 5 cm À1 and they are also commercially available.…”
Section: Introductionmentioning
confidence: 99%
“…A. Araujo et al, 15 worked on increasing light trapping in thin lm solar cells by depositing silver nanoparticles at rear surface of cells thus increasing the absorption up to 90% in light spectrum ranging 450-700 nm. Q. Luo et al, 7 proposed the integration of gold on TiO 2 nanospheres in porous layers of TiO 2 as well as perovskite to increase the power conversion efficiency to 18.24% thus making an improvement of 44% over the reference model. The absorption efficiency was measured for this model in the wavelength ranging from 300 to 800 nm.…”
Section: Introductionmentioning
confidence: 99%
“…These perovskite materials possess some fascinating properties, such as tunable bandgap (Noh et al, 2013), high absorption coefficients (Xing et al, 2013), long charge carrier (electron-hole) diffusion length (Stranks et al, 2013), and low-temperature solution processability (Wang et al, 2014). Over the past few years, numerous efforts and extensive investigations have been made into the morphology control of each functional layer (Haque et al, 2017;Yang et al, 2016), compositional engineering of perovskite materials (Hao et al, 2014;Jeon et al, 2015), device structure design (Burschka et al, 2013;Lee et al, 2012;Gao et al, 2014;Cao and Xue, 2014;Tan et al, 2014;, crystallization modulation of perovskites (Jeon et al, 2014;Xiao et al, 2014;Im et al, 2014) and interfacial engineering (Zhou et al, 2014;Luo et al, 2017;Assadi et al, 2018). Consequently, the power conversion efficiencies (PCEs) of PSC devices have been boosted from 3.8% to 22.7% under 1 sun conditions (100 mW cm −2 AM 1.5G) (Green et al, 2018).…”
Section: Introductionmentioning
confidence: 99%